Jim Henson's tale of sand - Pérez, Ramón, 1973- (Archaia Entertainment, 2011)
An original graphic novel adaptation of an unproduced, feature-length screenplay follows scruffy everyman Mac, who wakes up in an unfamiliar town and is chased across the desert of the American Southwest by all manners of man and beast of unimaginable proportions.